FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. GARUDA INDONESIA PEKANBARU - ", Gusnetti; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is to know what are the factors that influenced of the employee performance in PT. Garuda Indonesia Pekanbaru and what is the most dominant factor that influenced to the employee performance in PT. Garuda Indonesia Pekanbaru.This research used a qualitative descriptive method to analyzed the problem. Sample in this research are 50 respondents, and the data collected by observations, interviews and questionnaire. By using likert scale as the counting appliance to decided the length of intervalsBased on the result of research, factors which influenced of the employee performance in PT. Garuda Indonesia Pekanbaru has two factors, they are individual factor and organizations endorsement. The most dominant factor is the wages and salary factor from the individual factor and the harmonious working relationship who from organizations endorsement factor. And based of respondents, the individual factor such as education and experience does not influence too much to their performance when they are working.Keywords : human resource, performance, factors that influenced of the employee performance.